KH M. MUSTAQIM DAN PENGEMBANGAN NAHDLATUL ULAMA DI LAMONGAN 1992-2012 - Afran Dicky Triwibowo (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2018)
Abstract: The discussion in this article is about the role of an NU kiai in Lamongan. The focus of the discussion in this study is summarized in the formulation of the problem, namely; 1) What is the biography of K.H M. Mustaqim, 2) What was the condition of NU before 1992. 3) What was the important role of KH. M. Mustaqim in developing NU in Modo District. The research study was carried out using a diachronic historical approach assisted by theories from sociology. While the theory used is the Role Theory of Soerjono Soekanto. Based on historical knowledge, the authors use 4 methods, namely: heuristics, verification, interpretation, historiography. The conclusions from the research conducted are: (1) KH. M. Mustaqim was born in Modo, Lamongan on March 15, 1965. He is an active figure in Nahdlatul Ulama. He was the caretaker of the Bustanul Muta'allimin Islamic Boarding School, Chairman of the NU MWC Tanfidziyah 1992-2012, Deputy Chief of Lamongan PCNU. He has served in several organizations and other institutions. (2) MWC NU Modo was formed in 1951 and experienced ups and downs until 1992. During this period, MWC NU Modo underwent management changes 3 (three) times. (3) In the leadership of KH. M. Mustaqim succeeded in developing NU in the fields of: NU Modo MWC Building, NU al-Ikhsan Mosque, NU clinic, MI Ma'arif NU, MTs. Ma'arif NU, MTs. Asrorus Syifa', SMP NU, MA Ma'arif NU, MA Darul Ulum, SMA NU, SMK NU Mamba'ul Ulum, TPQ and Al-Ikhsan Islamic Boarding School. Keywords: kiai, NU, organization